THE CHALLENGES FACED BY EFL TEACHERS IN IMPLEMENTING SCHOOL LITERACY PROGRAM DURING THE COVID-19 PANDEMIC - Luh Putu Sonia Dewi; I Made Hery Santosa; Anak Agung Gede Yudha Pratama (Program Studi Pendidikan Bahasa Inggris Fakultas ilmu Budaya, 2022)
School Literacy Program is expected to be able to develop students' interest in reading. However, in practice, schools can still not achieve these goals indicated by the existence of challenges in its implementation. Thus, this study aimed at describing the challenges faced by EFL teachers in implementing school literacy programs during the COVID-19 pandemic. Conducting a descriptive qualitative study, four EFL junior high school teachers were interviewed using a semi-structured interview. The results of the study show that the EFL teachers were challenged by four factors in implementing the school literacy program during COVID-19, namely, 1) students' interest in reading, 2) the technical challenges, 3) the teacher's lack of understanding about the school literacy program, 4) time management. These four factors were considered some of the challenges, such as students read in order to fulfil the obligation to fill out daily journals, not because of their own desires, technological illiteracy, and inadequate source of online reading. Therefore, the practitioners of school activities can respond and take thoughtful actions regarding the problems they face in implementing the school literacy program.